Content Strategies to Improve the Performance of Audio Streaming Services: Focusing on Content Genre and Update Features - Minjeong Ham; Kyu Tae Kwak; Hwaseong Na; Sang Woo Lee (SAGE Open)
The AuSS market witnessed substantial growth in 2022, with a strong estimated annual expansion from 2023 to 2030. Prominent companies like Amazon, Spotify, and YouTube are intensifying their competition by acquiring smaller firms in the audio content industry. To navigate this intense AuSS market competition, this study aims to categorize AuSS content genres and investigates the impact of content genre and update features on content performance (measured by content usage and subscriber size). Based on econometric analysis, we explore how the relationship between content genre and content performance is influenced by content update features. Empirical data was collected from Naver’s Audioclip, South Korea’s leading internet portal. For the research results, the content performance was different depending on the content genre. The more the regularity and frequency of content updates, the better the content performance. The effect of content update frequency on content performance differed by each content genre. Based on the findings of this study, we suggest the academic and managerial implications for content strategies to enhance the AuSS content performance of related companies.